High‐flow nasal cannula oxygen therapy: Alternative respiratory therapy for severe post‐transplant hypoxemia in children with hepatopulmonary syndrome. (25th October 2020) - Hamada, Satoshi; Okamoto, Tatsuya; Ogawa, Eri; Sonoda, Mari; Okajima, Hideaki; Hirai, Toyohiro; Handa, Tomohiro; Uemoto, Shinji; Chin, Kazuo
Abstract: Severe post‐transplant hypoxemia, which is defined as <50 mm Hg of the partial pressure of oxygen in arterial blood/fraction of inspired oxygen (P/F) ratio, is a major post‐operative complication with high mortality rates in patients with hepatopulmonary syndrome (HPS). Non‐invasive positive pressure ventilation therapy and mechanical ventilation are options for respiratory support of patients with severe post‐transplant hypoxemia. However, these therapies are associated with several problems, such as compliance, ventilator‐associated pneumonia, and lung injury. We here firstly described two children with HPS who developed severe post‐transplant hypoxemia (lowest post‐operative P/F ratio, 49.7 and 34.0 mm Hg, respectively) that was successfully managed with high‐flow nasal cannula (HFNC) oxygen therapy and vasodilation drugs without adverse complications or necessity of reintubation. We consider that HFNC oxygen therapy could become a safe alternative respiratory therapy or be added to the other such as inhaled nitric oxide (iNO), methylene blue (MB), inhaled epoprostenol, embolization of abnormal pulmonary vessels, and combination of iNO and MB for severe post‐transplant hypoxemia in children with HPS.